Psychosocial adjustment infertility: A comparision study of infertile couples, couples undergoing assisted reproductive technologies and presumed fertile couples - Ramos, Mariana Moura (2010)
The aim of the present study was to investigate psychosocial adjustment and infertility related stress of infertile couples and couples undergoing Assisted Reproductive Technologies (ART). In a cross sectional study, 148 couples were recruited: 79 couples undergoing ART, 25 infertile couples in their first medical appointment in an infertility centre and no previous ART treatments and 44 childless couples in reproductive age without infertility history. Measures assessed emotional adjustment, quality of life, marital relationship and infertility stress. Couples were the focus of the analysis. Results indicated that couples undergoing ART presented more adjustment difficulties, especially women. No significant differences were found in marital adjustment, althoughART couples idealized their marital relationship to a higher degree. Results are discussed in terms of clinical implications and future research directions. ------ RESUMO ------ O objectivo deste estudo foi investigar o ajustamento psicossocial e o stress associado à infertilidade em casais inférteis e casais que recorreram à Reprodução Medicamente Assistida (RMA). Neste estudo transversal, a amostra foi constituída por 148 casais: 79 casais a realizar tratamento de RMA, 25 casais inférteis, sem tratamentos de RMA anteriores, na sua primeira visita a um serviço de infertilidade e 44 casais em idade reprodutiva, sem filhos e sem história de infertilidade. Foi avaliado o ajustamento emocional, a qualidade de vida, a relação conjugal e o stress associado à infertilidade. Os resultados indicaram que os casais, principalmente as mulheres, que estão a realizar um tratamento de RMA apresentam maiores dificuldades de ajustamento. No que se refere ao relacionamento conjugal, de um modo geral não foram encontradas diferenças, apesar de os casais que recorreram à RMA tenderem a idealizar mais o seu relacionamento conjugal. As implicações clínicas e futuras áreas de investigação são discutidas.